A non-iterative approach for maximum power extraction from PEM fuel cell using resistance estimation. (1st May 2019) - Bankupalli, Phani Teja; Ghosh, Subhojit; Kumar, Lalit; Samanta, Susovon; Dixit, Tata Venkat
Highlights: A non-iterative approach proposed for maximum power extraction from PEMFC. MPPT boost converter designed for faster response and ripple minimization. Online resistance measurement scheme for MPPT with minimum computation effort. Direct duty ratio estimation for MPP unlike gradient or search based approaches. Proposed method validated experimentally. Abstract: A primary challenge towards the adoption of Polymer Electrolyte Membrane Fuel Cell (PEMFC) on a wider scale involves the extraction of maximum power irrespective of variation is source and loading condition, commonly referred to as Maximum Power Point Tracking (MPPT). The non-linear voltage current relationship and dynamic variation of maximum extractable power with change in operating parameters makes MPPT task quite challenging. Motivated by the need to achieve MPPT over a wider operating range with reduced computational burden, this paper proposes a non-iterative approach for maximum power extraction from PEMFC. Continuous estimation of resistance across the source and load by monitoring the voltage and current, allows reducing the deviation between equivalent resistance across the PEMFC terminals and its internal resistance by regulating the Pulse Width Modulated DC-DC converter. The power converter for MPPT is designed with the objective of simultaneously minimizing the ripple content and achieving faster dynamic response. The proposed approach is compared with the Incremental Resistance Method (INR), in terms of simplicity, MPP efficiency and better dynamic response for both source and load perturbations. The effectiveness of the proposed scheme has been validated experimentally.